Exploring Intra-Group Income Convergence for the Central Asian Countries - Gul, Hameed; Haq, Ihtisham ul; Khan, Dilawar (iRASD Journal of Economics, 2022)
The main objective of this study is to explore income convergence for the Central Asian countries whereas income convergence refers to the state when all nations in a region converge to the identical level of steady state in terms of per capita. This study tested the income convergence through beta convergence and sigma convergence over period from 2003 to 2019. The beta convergence indicates that the poor economies grow more rapidly than the rich nations and catch up with them in terms of per capita income, whereas sigma convergence means that the gaps between the per capita incomes of the nations in the region decrease over the passage of time. The beta convergence is determined through panel unit root tests, whereas sigma convergence is determined through the coefficient of variation. This study finds beta convergence as well as sigma convergence henceforth; income convergence is confirmed in Central Asian countries. It can be concluded that economic integration is in favor of Central Asia, so it is recommended that these nations must ensure economic cooperation with each other through easing trade restrictions and lessening import taxes on imports. Moreover, it will also be helpful to ensure the free mobility of the labor force among Central Asian countries, as it will further help them to ensure economic integration and helps in reducing the income inequality in the region.